USING MIXED METHOD APPROACH TO UNDERSTAND ACCEPTANCE AND USAGE OF ICT IN NIGERIAN PUBLIC UNIVERSITY - David, Oye Nathaniel; N., A.Iahad; N., Ab.Rahim (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Technology acceptance is about how people accept andadopt some technology to use. The primary target ofmany technology acceptance studies is to examine how toencourage usage and also analyze what interruptsacceptance and usage of technologies. Using the mixedmethod approach, the quantitative phase shows that, theperceived usefulness (PE) is significant with p-value(.023) and the perceived ease of use (EE) is significantwith p-value (.001). These results shows that the intentionto accept and use ICT by the academic staff is a functionof various concepts including the understanding that ICTis useful and it is not difficult to use. However thequalitative phase shows that it is true that theacademicians intent to use ICT but the conditions andenvironment are not encouraging, classrooms are poorlydesigned. No regular power supply, no ICT facilities onground and poor internet connectivity. The mixed methodapproach has given the true picture of the acceptance andusage of ICT in Nigerian public university. Thequantitative phase shows the constructs that havesignificant influence on acceptance and use of ICT, whilethe qualitative phase interprets the in-depth meaning ofthe statistical results and the environmental challengesthat most be tackled to realize the full vision.